Fish hybridization: Enhancing genetic potential, ecological implications and ethical perspectives - Nur Nashyiroh Izayati Mastor; Wahidatul Husna Zuldin; Norfazreena Mohd Faudzi; Kenneth Francis Rodrigues; Julian Ransangan (A Publication of Unique Scientific Publishers, 2025)
Hybridization is an important tool in aquaculture to combine the desirable traits of parental fish stocks. This process produces offspring with disease resistance, improved feed conversion efficiency, accelerated growth, environmental resilience and superior flesh quality. All these traits are economically beneficial and can fulfill large demands in the industry without depleting wild stocks. Various techniques have been used to hybridize fish, including artificial insemination, selective mating and genetic manipulation. Molecular methods like gene editing and in-vitro fertilization can ensure speedy production of hybrid stocks with precise traits, but the processes should be supported by impact studies to provide a comprehensive understanding of hybridization outcomes. This review explores the diverse methods of fish hybridization in aquaculture, highlighting examples of their genetic and physiological impacts on wild fish populations, besides their ecological and evolutionary consequences. It also explores ethical considerations and public perception, particularly gene modification, along with an analysis of regulatory and policy frameworks. As global demand for food protein continues to rise, aquaculture is increasingly recognized as a sustainable solution to meet the demand. The increasing potential of hybrid species in enhancing aquaculture production underscores the importance of developing efficient and sustainable industry practices